The Impact of the Clinical Audit Cycle on the Implementation of Hospital Triage in the Emergency Department - Taban, Farzad; Shariati, Abdol Ali; Molavynejad, Shahram; Haghighizadeh , Mohammad Hossein (Advances in Nursing & Midwifery, 2024)
Abstract Introduction: As the first step in dealing with patients referring to the emergency department, the triage process prioritizes these patients and classifies them to different levels of triage based on the severity of their clinical conditions. This prioritization is aimed at distinguishing patients whose treatment can be delayed without experiencing any complications from those who need immediate action and delay in whose treatment will cause serious complications. Therefore, this study aimed to determine the effect of the clinical audit cycle on the implementation of hospital triage in the emergency department of Golestan Hospital in Ahvaz in 2018. Methods: This was a quasi-experimental study the population of which included all events related to the way hospital triage was implemented for patients referring to the emergency department of Golestan Hospital of Ahvaz, southwest of Iran. The research sample included 385 triage events performed for patients referring to the emergency department. A researcher-made triage questionnaire was used to check nurses’ accuracy in four dimensions, namely taking history, taking vital signs, determining triage level, and frequency distribution. SPSS version 23 was used to analyze the data. A significance level of α = 0.05 was adopted for this study. Results: Before the intervention, the mean scores of the intervention group in terms of Checklist dimensions were as follow: taking history (11.26 ± 1.89), vital signs (15.62 ± 2.21), determining triage level (23.56 ± 7.95), determining the level of required facilities (9.11 ± 3.27), and doing the general triage of patients (55.56 ± 10.17). After the intervention, the mean scores in the intervention group were as follows: taking history (12.36 ± 2.71), vital signs (16.81 ± 3.31), determining triage level (30 ± 0.051), determining the level of required facilities (11.99 ± 0.072), and doing the general triage of patients (64.73 ± 10.9), which shows the positive impact of the intervention (P < 0.001). Conclusions: According to the findings of the present study, appropriate training in triage along with strict control and monitoring of the hospital triage implementation process and its prioritization will lead to provision of better medical services. Also, patients whose treatment can be delayed without experiencing any complications can be distinguished from those who need immediate action.